Ingested microplastics (>100 μm) are translocated to organs of the tropical fiddler crab Uca rapax. Issue 1 (15th July 2015) - Brennecke, Dennis; Ferreira, Erica C.; Costa, Tarso M.M.; Appel, Daniel; da Gama, Bernardo A.P.; Lenz, Mark
Highlights: Microplastic fragments were found in gills, stomach and hepatopancreas of Uca rapax . Retention was not influenced by fragment preweathering and fragment abundance. Presence of microplastics in organs shows their potential to harm marine organisms. Abstract: Microplastics, which are accumulating in marine sediments, are assumed to pose a risk for deposit feeding invertebrates. We tested whether the fiddler crab Uca rapax ingests and retains microplastics in its body. Furthermore, we investigated whether retention rates depend on (a) the quality of the marine environment in which the plastics were pre-weathered and on (b) their abundance. For this, polystyrene pellets were submersed at a polluted and a pristine site near Niterói, Brazil, for 2 weeks. Then specimens of U. rapax were, in laboratory experiments, exposed to fragments (180–250 μm) derived from these pellets for 2 months. After this period, microplastics were observed in the gills, stomach and hepatopancreas of the animals. However, fragment retention was not influenced by the two factors that we manipulated. The presence of microplastics in different organs of the crab supports the assumption that these particles have the potential to harm marine invertebrates.